A Study on Performance Related Pay of Foreign Financial Multinational Companies in China - Xiao, Erde (2007)
Many foreign financial and professional service institutions believe that China will become one of their biggest global markets. Since accession to the WTO, the Chinese financial industry has been greatly opened to foreign financial institutions; this has attracted many financial firms operating in this market. However, high employee turnover rate in this industry has been reported.